Migrations, admixture and genetic diversity in Central Argentinian Patagonia: analysis of autosomal Alu polymorphisms - Parolin, María Laura (2017)
This study aimed to analyze autosomal Alu insertions in three localities from Patagonia Argentina belonging to the Andes region and the coast of the Chubut province. Knowledge of the genetic diversity of these populations, along with the genealogical data, will contribute to better understand historical information, differential migration process and bio-demographic composition of the Central Patagonia region. In order to achieve this objective, 16 autosomal Alu insertion polymorphisms were genotyped: ACE, APO-A1, TPA25, FXIIIB, A25, HS4.32, D1, HS4.69, HS2.43, Sb19.12, Yb8NBC120, Sb19.3, Yb8NBC125, Ya5NBC221, DM, and CD4. Our results showed that the Central Patagonia region presents a complex continental genetic admixture with marked Native American roots (39% ± 1.2), Eurasian (56% ± 1.73) and, to a lesser extent, African (5% ± 1.7). The genetic proximity of the Patagonian samples in relation to groups from Europe and Northern Africa, but with a displacement towards the native communities, constitutes a clear indicator of the differential admixture process that took place in different regions of Argentina. Moreover, genetic differences were observed between Patagonian localities and Bahía Blanca (Central region of Argentina). These observations warned us that population genetic constitution analysis cannot be approached without bearing in mind the regional particularities, which are the result of the different historical, migratory, social-economic and demographic processes that occurs in the country.